Crowdsourcing peer information to change spending behavior - D’Acunto, Francesco; Rossi, Alberto G.; Weber, Michael (Journal of Financial Economics, 2024)
We isolate the information channel of peer effects in consumption in a setting that excludes a role for common shocks or social pressure—a spending panel paired with crowdsourced information about anonymous “peers” elicited at different times. Consumers converge to peers’ spending, and more so when peer signals are more informative. Convergence is asymmetric: within 12 months of information provision, overspenders close 17% and underspenders 5% of their gap relative to peers. We exploit the quasi-random assignment to peer groups in an instrumental-variable strategy and implement an experiment for external validity. Our results are consistent with information-based theories of overconsumption.